2016
DOI: 10.1080/15295192.2016.1158600
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Multi-Informant Assessment Measures of Parental Monitoring and Their Links With Adolescent Delinquent Behavior

Abstract: SYNOPSIS Objective Parents’ poor monitoring of adolescents’ whereabouts and activities is commonly linked to adolescents’ increased engagement in delinquent behaviors. Yet, different domains of parental monitoring (parental monitoring behaviors vs. parental knowledge) and reports from multiple informants (parent vs. adolescent) may vary in their links to delinquent behavior. Design Seventy-four parental caregivers and 74 adolescents completed survey measures of parental monitoring and knowledge, and adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…As such, only adolescents and their mothers (n = 141 adolescent-mother dyads) were included in this study. However, a focus on discrepancies between adolescent and mother reports is consistent with prior work in the informant discrepancies literature (see Augenstein et al 2016;De Los Reyes et al 2013a, b, c;De Los Reyes et al 2010;Laird and De Los Reyes 2013).…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…As such, only adolescents and their mothers (n = 141 adolescent-mother dyads) were included in this study. However, a focus on discrepancies between adolescent and mother reports is consistent with prior work in the informant discrepancies literature (see Augenstein et al 2016;De Los Reyes et al 2013a, b, c;De Los Reyes et al 2010;Laird and De Los Reyes 2013).…”
Section: Methodsmentioning
confidence: 70%
“…Although most adolescents experience positive relationships with their families (Smetana et al 2006), as adolescents negotiate more autonomy with parents, family satisfaction and cohesion decrease (Ohannessian et al 2000;Smetana et al 2006;Steinberg and Morris 2001), and family conflict increases (Montemayor 1983). As levels of family conflict rise, disagreements between adolescents and their parents increase as well (De Los Reyes et al 2012), including differences in how adolescents and their parents perceive the family and their relationships with one another (Augenstein et al 2016;De Los Reyes et al 2016;De Los Reyes 2011;Ohannessian et al 2000). For example, a mother might view herself as knowledgeable about her adolescent's friends and the whereabouts of her adolescent, whereas the adolescent might perceive the mother's level of knowledge as very low (De Los Reyes et al 2013d).…”
Section: Introductionmentioning
confidence: 93%
“…Ethnic/racial demographic rates total above 100% because parents could select multiple response options. As in prior work (e.g., Augenstein et al, ; De Los Reyes et al, ; De Los Reyes, Augenstein, Aldao, et al, Deros et al, ; Rausch et al, ; Thomas et al, ), parents provided data about weekly family income using a survey that included response options on a 10‐point Likert‐type scale in $100 increments (e.g., $101–$200 per week). On this scale, parents reported that 29 of the families earned $500 or less per week, 23 earned between $501 and $900 per week, and 44 earned more than $901 in income per week (“$901 + per week” was the sample's modal response).…”
Section: Methodsmentioning
confidence: 99%
“…Other approaches possess similar capabilities and have been successfully implemented in the study of informant discrepancies. These include metaanalysis of cross-informant correspondence (e.g., Achenbach et al 1987;De Los Reyes et al 2015b), direct assessment of discrepant views (i.e., via structured interview: De Los Reyes et al 2012, 2013d, nested repeated measures analytic models (e.g., generalized estimating equations; Alfano et al 2015;Augenstein et al 2016;De Los Reyes et al 2013b); and person-centered models (e.g., latent class analysis; De Los Reyes et al 2009, 2011, 2016a, 2013aLippold et al 2011Lippold et al , 2013Lippold et al , 2014. In line with this recent work, a key aim of this Special Issue is to report recent work on discrepancies between adolescents' and parents' reports of family functioning, using these emerging measurement and analytic models.…”
Section: Importance Of Sound Approaches To Modeling Informant Discrepmentioning
confidence: 99%